Peran Ibu Rumah Tangga Dalam Peningkatan Ekonomi Keluarga Melalui Bisnis Digital Pasca Covid-19 - Elli Ruslina; Siti Rodiah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The family economy is one source that can increase the family's welfare. The crisis caused by the Covid- 19 pandemic has exacerbated life in the household, thus demanding a change in behavior in a family's life. Prosperous survival of the role of the wife as a housewife is required to participate in the struggle for survival, especially in increasing economic needs. Economic needs include developing skills in the field of business, to be able to generate income, namely making food production, including pizza type foods which are currently in vogue, especially as snacks and side dishes. The problems faced in product development include the need for skills in marketing, and having to know the market share of the products offered. Marketing and market share is an obstacle in charging these products, so it requires a study that can open up better opportunities. The purpose of community service is to increase the role of housewives in improving the economy, especially the family economy through businesses using digital applications. The implementation method offered in product development includes several things that must be done, namely determining a strategic place other than the house as a place of production, strengthening in the field of capital, status of business entities that can provide added value, for example small and medium & micro businesses in the form of business entities individual; the status of recognition from the public for the products produced and following current trends with an electronic innovation. Involving digital technology partners can help marketing and expand market share. Data analysis uses secondary data in the form of laws and regulations and primary data through interviews. Strengthening the empowerment of the role of housewives who have produced a product needs to be carried out with various supports to support the economic progress of the family and also contribute to the economic growth of the community. Through outreach, briefings that involve related fields, for example regarding forms of supporting business entities, utilization of intellectual property rights, and new innovations in the field of digital technology, as well as being able to join wider associations and have existing insights well.